Flow boiling heat transfer characteristics on micro-pin-finned surfaces in a horizontal narrow microchannel. (15th September 2022) - Ma, Xiang; Ji, Xinyu; Wang, Jinyu; Fang, Jiabin; Zhang, Yonghai; Wei, Jinjia
Highlights: An experimental investigation of flow boiling on micro-pin-fined surfaces in a horizontal narrow microchannel was performed. The CHF and HTC were enhanced up to 51% and 240%, respectively. The bubble behaviors were captured to explain the heat transfer enhancement mechanism. A new correlation was proposed to predict flow boiling HTC in the microchannel by considering the micro-pin-fins. Abstract: In this paper, an experimental investigation of flow boiling in a horizontal narrow microchannel with hydraulic diameter of Dh  = 952 μm was conducted. Flow boiling heat transfer characteristics of micro-pin-finned surfaces were evaluated over the mass fluxes range from 200 - 500 kg/m 2 s (corresponding flow velocity: 0.2 - 0.5 m/s), using deionized water as the working fluid with different inlet temperatures Tin  = 30 - 50 °C. The outlet pressure of the microchannel was about 1 atm. The boiling curves, heat transfer coefficients, bubble behaviors and heat transfer enhancement mechanism were discussed with the variation of heat flux, mass flux and inlet temperature. The results indicated that the micro-pin-finned surfaces could improve the critical heat flux (CHF) and heat transfer coefficient (HTC) greatly due to numerous nucleate sites and large heat transfer area enhancement ratio. The CHF up to 360 W/cm 2 has been demonstrated at a mass flux of 500 kg/m 2 s. Compared with a smooth surface, a 240% higher heat transfer coefficient (18.4 W/cm 2 K) on the S30-120 surface has been achieved at a mass flux of 500 kg/m 2 s with an inlet temperature of 30 °C. The boiling curves of the micro-pin-finned surfaces presented an obvious "hook back" phenomenon after reaching the onset of the nucleate boiling (ONB) and then the wall temperature had a slight rise with the increase of the heat flux. Moreover, the intensive micro-pin-finned arrangements showed a significant wicking effect and promoted liquid replenishment, which could destroy the liquid boundary and enhance turbulence. The bubble behaviors were also captured to explain the heat transfer enhancement mechanism in a horizontal narrow microchannel.